A study of cytohistological correlation of equivocal or atypical proliferative breast lesions at a tertiary care institution of North India - Kapil, Raman; Gill, Meenu; Malik, Sucheta; Singh, Lalit; Gupta, Sumiti; Sen, Rajeev (International Journal of Research in Medical Sciences, 2022)
Background: Fine needle aspiration cytology is the mostly the first diagnostic test used for the diagnosis of breast masses. But there is morphological overlap among the sequential lesions from the precancerous group to frank carcinoma known as “grey zone”. This grey zone in cytology is estimated to constitute 8.9% of cases. Methods: Smears were prepared from the fine needle aspirates and stained with Leishman/Giemsa. Trucut biopsy, mastectomy or MRM specimens of patients diagnosed as having on cytology benign with atypia (C3) /suspicious of malignancy (C4) were subjected to histopathological evaluation and cytohistopathogical correlation was done in these cases. Results: 75% of patients who belonged to category C3 had benign lesions, whereas about 90% of those in category C4 had malignant diagnosis. This difference was statistically significant. Conclusions: Combination of the mammography and cytology along with the clinical findings (the "triple test") allows for proper management for each patient, determining which patient should undergo surgery and which patient needs close follow-up, hence avoiding an unnecessary surgery. And the patients in cytology category C4 must have the diagnosis confirmed by histological examination.